2022
DOI: 10.3390/molecules27133972
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Asian Propolis Compounds as Potential Anti-Type 2 Diabetes Mellitus Agents by Using Inverse Virtual Screening with the DIA-DB Web Server, Tanimoto Similarity Analysis, and Molecular Dynamic Simulation

Abstract: Propolis contains a wide range of pharmacological activities because of their various bioactive compounds. The beneficial effect of propolis is interesting for treating type-2 diabetes mellitus (T2DM) owing to dysregulation of multiple metabolic processes. In this study, 275 of 658 Asian propolis compounds were evaluated as potential anti-T2DM agents using the DIA-DB web server towards 18 known anti-diabetes protein targets. More than 20% of all compounds could bind to more than five diabetes targets with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 177 publications
0
5
0
Order By: Relevance
“… 29 We found that neobavaisoflavone, methylophiopogonone A, 3’-methoxydaidzin, and genistin as novel candidates for anti-SARS CoV-2 infection through inhibition of S2 and Mpro, 48 whereas (RR)-(+)-30-senecioylkhellactone and pinobanksin-3-O-butyrate as novel aldose reductase inhibitors in the treatment of type-2 diabetes mellitus. 31 Moreover, diosmetin, cosmosiin, genistin, and 3’-methoxy-5’-hydroxyisoflavone-7-O-β-D revealed as novel candidates for inhibition of Streptococcus mutans activity in caries. 29 We also found that isoetin poses strong binding interaction to AChE, Caspase3, MAPK14, NF-kB, and TNF-α that related to neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“… 29 We found that neobavaisoflavone, methylophiopogonone A, 3’-methoxydaidzin, and genistin as novel candidates for anti-SARS CoV-2 infection through inhibition of S2 and Mpro, 48 whereas (RR)-(+)-30-senecioylkhellactone and pinobanksin-3-O-butyrate as novel aldose reductase inhibitors in the treatment of type-2 diabetes mellitus. 31 Moreover, diosmetin, cosmosiin, genistin, and 3’-methoxy-5’-hydroxyisoflavone-7-O-β-D revealed as novel candidates for inhibition of Streptococcus mutans activity in caries. 29 We also found that isoetin poses strong binding interaction to AChE, Caspase3, MAPK14, NF-kB, and TNF-α that related to neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…NSC-94258, as an antineoplastic agent, its protein targets are AKR1B1 , CYP19A1 , HSD17B1 . Aldo-ketoreductase family 1, member B1 (AKR1B1), can prevent complications of diabetes and improve insulin sensitivity by catalyzing the reduction of glucose to sorbitol ( Zhan et al, 2019 ; Syaifie et al, 2022 ). In GCs, androstenedione and testosterone act as substrates and are converted by CYP19A1 to estrogen, the mutation of CYP19A1 may lead to the occurrence and the development of hyperandrogenemia in PCOS ( Kumariya et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies also identified numerous flavonoid and phenolic acid compounds in propolis extract [ 71-73 ]. We have also explored 658 Asian propolis compounds that are majorly in the group of flavonoids, phenolic acid, and terpenoids [ 74 ]. The chemical structures of flavonoids and phenols group are presented in Figure 1 .…”
Section: Active Compounds Of Propolismentioning
confidence: 99%